Avaliação do impacto do acesso aberto em periódicos da área da Ciência da Informação : uma análise de indicadores bibliométricos e altmétricos - Cintra, Paulo Roberto (2017)
The existence of innumerous barriers to access scientific knowledge gave rise to the movement in favor of open access. The impact of scientific research tends to be measured by the total number of citations the work gets, and so the hypothesis of a possible Open Access Citation Advantage (OACA) emerged, in which it is argued that the articles available in open access have an advantage in the number of citations in relation to those only available in restricted publications. However, assessing the impact of a scientific publication must go beyond the analysis of citations, as it is necessary to consider that scientists do not cite all references that may have influenced them during the research, and that other actors are also part of the scientific community. For these reasons, the use of alternative metrics to assist the evaluation of science has been discussed in a new subfield called Altmetrics. In this sense, the aim of this study was to investigate the potential benefits that open access can offer to the field of Information Science. Therefore, bibliometric citation indicators and altmetric indicators for four journals were collected and analyzed: Journal of the American Society for Information Science, Scientometrics, El Profesional de la Información and Transinformação. Data sources covered Web of Science, Google Scholar, Altmetric.com and Mendeley. The results indicated that open access actually offered advantages over the average number of citations and references in the social web received in all hybrid journals. This fact confirms the validity of the OACA hypothesis for the Information Science area. It was also found that this advantage is maintained, at least, until the eighth year after publication, and it extends to the altmetrics data.